Pemilihan Desain Penutup Pintu Menggunakan Metode Pugh - TB. U. Adi Subekhi; Fahad Zaqi Mukmin; Choirul Anwar (Sekolah Tinggi Teknologi Wastukancana, 2022)
Abstract The door is the main access to enter a room, which can also affect the effectiveness and safety of users. This research contains 3 design concepts regarding door closings using the principle of a pure 4 rod mechanism. Of the 3 design concepts, the most superior concept was selected using the Pugh method. Several parameters used in the selection of the Pugh method are mass, ease of processing, kinematic mobility, and yield strength of the system for each concept. A superior concept is a concept that has a small mass and yield strength system but has a large safety factor. Based on the analysis and design concept conclusions, the yield strength of the connecting rod system is 204 MPa and the yield strength of the slider rail system is 27.6 MPa. And the yield strength that occurs does not exceed/exceed the yield strength of the material used. The yield strength of galvanized is 300 MPa and the yield strength of aluminum is 276 MPa. While the safety factor on the connecting rod = 300 / 204 = 1.4. and Safety factor on the slider rail = 276 / 27.6 = 10.